Spillover effects of rural residents’ past pro-environmental production behavior on their voluntary waste separation behavior - Yuhua Teng; Ning Li; Changjin Liu; Jing Yang; Yan Chen (Frontiers in Sustainable Food Systems)
Based on the survey data of rural residents in the National Ecological Civilization Pilot Area (Jiangxi), this paper empirically analyzes the spillover effect and mechanism of past pro-environmental production behavior on rural residents’ voluntary garbage sorting behavior, and adopts the fsQCA to clarify the grouping paths and examines the interactive relationship among multiple factors. The results of the empirical study show that: firstly, past pro-environmental production behaviors can directly promote rural residents’ voluntary garbage sorting behaviors; secondly, environmental self-identification and subjective norms have a partially mediating effect; thirdly, publicity and village regulations play a positive moderating effect. Further, the results of fsQCA analysis reaffirm the influence mechanisms, and reveal the multiple concurrent pathways through which past pro-environmental production behaviors drive the active waste sorting behaviors of rural residents. It’s found that there is a substitution relationship between rural residents’ past pro-environmental production behavior and publicity and education. This study enriches the theoretical explanation of the spillover of residents’ pro-environmental behaviors, and provides useful ideas for stimulating rural residents’ enthusiasm in active participation of rural residents in household waste sorting.